Electric organ discharges of South African Marcusenius species (Teleostei: Mormyridae) and their effectiveness as indicators of local species diversity - Kramer, L. Bernd; Maake, Pholoshi A.; Gon, Ofer (Zootaxa, 2016)
Recent morphological and genetic studies have revealed two new species of snoutfish in South Africa, Marcusenius caudisquamatus and M. krameri, which had been confused with M. pongolensis, the South African bulldog fish. All known mormyriform fish are nocturnal and emit electric organ discharges (EODs) for communication that are characteristic for their species. This paper examines whether or not the EODs of these three closely-related South African species can be differentiated from each other. An EOD pulse of a bulldog fish consists of a head-positive phase P, followed by a head-negative phase N of short duration. We measured and compared six variables of the EOD pulse waveform for South African samples for the three species from different locations using MANOVA, ANOVA and Discriminant Analysis, with M. devosi from Kenya as an outgroup. The EOD waveforms, normalized to the same P-phase amplitude, varied significantly from each other in four variables, most strongly in the amplitude of the N phase and the duration of the P phase. In two species, M. devosi and M. krameri, there was no evidence of difference between sexes, in contrast to M. pongolensis and M. caudisquamatus whose male pulses were of longer duration. M. devosi and M. krameri were statistically significantly independent of each other and of any other group studied. By contrast, the M. pongolensis specimens from different locations showed a high degree of variability amongst each other, including significant separation, and overlap with M. caudisquamatus.